Antimycobacterial and antitumor activities of Palladium(II) complexes containing isonicotinamide (isn): X-ray structure of trans-[Pd(N-3)(2)(isn)(2)] - de Souza, Rodrigo A. [UNESP]; Stevanato, Alessandra [UNESP]; Treu-Filho, Oswaldo [UNESP]; Netto, Adelino Vieira de Godoy [UNESP]; Mauro, Antonio Eduardo [UNESP]; Castellano, Eduardo E.; Carlos, Iracilda Z. [UNESP]; Pavan, Fernando R. [UNESP]; Leite, Clarice Q. F. [UNESP] (Elsevier France-editions Scientifiques Medicales Elsevier, 2010)
Complexes of the type trans-[PdX2(isn)(2)] {X = Cl (1), N-3 (2), SCN (3), NCO (4); isn = isonicotinamide} were synthesized and evaluated for in vitro antimycobacterial and antitumor activities. The coordination mode of the isonicotinamide and the pseudohalide ligands was inferred by IR spectroscopy. Single crystal X-ray diffraction determination on 2 showed that coordination geometry around Pd(II) is nearly square planar, with the ligands in a trans configuration. All the compounds demonstrated better in vitro activity against Mycobacterium tuberculosis than isonicotinamide and pyrazinamide. Among the complexes, compound 2 was found to be the most active with MIC of 35.89 mu M. Complexes 1-4 were also screened for their in vitro antitumor activity towards LM3 and LP07 murine cancer cell lines. (C) 2010 Elsevier Masson SAS. All rights reserved.
Keywords: Palladium(II) complexes; Isonicotinamide; Cytotoxicity assays; Antimycobacterial; Antitumor activity